Biomonitoring of a worker population exposed to platinum dust in a catalyst production plant - Petrucci, F; Violante, N; Senofonte, O; Cristaudo, A; Di Gregorio, M; Forte, G; Alimonti, A (Occupational and environmental medicine (London, England), 2005)
Aims: To evaluate the occupational exposure to platinum in an industrial plant engaged in the production, recovery, and recycling of catalytic converters for the automotive traction and chemical industries. Methods: Pt was determined in airborne particulate matter, and blood, urine, and hair of 106 exposed workers, 21 controls from the plant’s administrative offices, and 25 unexposed subjects. Results: The highest air Pt level was found in the department of the plant in which supports are coated with acid metal solutions, where values of 2.39 and 4.83 μg/m3 respectively were found in environmental airborne particulate matter and in air collected using personal sampler devices. The percentage of soluble Pt was also highest in this area, varying from 24% to 44% of the total. The biological data confirmed this trend, with mean concentrations in this site being higher than in other working areas: 1.86 μg/l (urine), 0.38 μg/l (blood), and 2.26 μg/kg (hair). The workers employed in the administrative sector, who were not directly exposed to Pt, had levels of contaminant lower than those of other workers, albeit 2–20 times higher than those of external controls. High correlations were obtained between Pt levels detected in airborne samples using personal devices and those found in urine and hair, but not in blood. Conclusions: The background level of Pt in all areas of the factory implies widespread exposure for the workers. The most reliable biomarker was urine. Hair cannot be considered a good index of time related exposure, at least until more reliable methods of washing can be found that are able to remove exogenous Pt completely.